Efeito do tipo de corrente usada em soldagem GMAW na resistência ao riscamento de depósitos de Fe-Cr-C - Melo, Vinicius Santos (2018)
Abrasive wear leads to high costs in industrialized countries, especially on extraction and processing industries of mineral and agriculture. The use of protective coatings in order to decrease its effects is widely used in these cases. However, protective coating quality is highly linked to the process used for its manufacture. The GMAW (Gas Metal Arc Welding) welding process is widely applied for protective coatings deposition, resulting good deposition rate and facility of its use. The development of new welding sources capable of changing the shape of the electric current allowed the creation of two types of current: pulsed and double pulsed / pulsed thermal, both resulting in a greater control of metal deposition on the fusion pool. Aiming to analyze the influence of these new types of current on the wear resistance, this work consisted of the production of hard coating deposits with the GMAW welding process with conventional, pulsed and pulsed thermal current with the same welding energy, with a macrostructural, microstructural, mechanical characterization and the abrasive wear characteristics of the samples. Analysis of the abrasive wear was performed through a linear scratch test, and a morphological and tribological risk analysis was performed. It was observed that there was an influence of current type during manufacturing process at the macrostructure, microstructure and mechanics of the deposits, also, there was no phases alterations but on its deposit distribution. The results of the linear scratch test showed that there was no change in the coefficient of friction between the samples. As a consequence of the microstructural alteration, there was a morphology variation of the scratches and volume worn, and the pulsed current presented the best values of volume worn and the thermal pulsed current had the best risk morphology.